The Financial Trilemma - Dirk Schoenmaker (Tinbergen Institute, 2011)
The financial trilemma states that financial stability, financial integration and national financial policies are incompatible. Any two of the three objectives can be combined but not all three; one has to give. This paper develops a model to underpin the financial trilemma. Our findings for financial integration suggest that the financial trilemma is in particular at work in Europe.
Keywords: F33; G28; H41; 330; Financial Stability; Public Good; Finanzpolitik; Finanzmarktregulierung; Finanzkrise; Politisches Ziel; Wirkungsanalyse; EU-Staaten